KARAKTERISTIK FISIOLOGI GALUR-GALUR PADI RAWA BENGKULU - Sumardi; Sari, Ganisa Ardhiani; Barchia, M. Faiz (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
Rice is the main source of carbohydrates in Indonesia, rice production decreases every year due to land conversion from agricultural land to non-agricultural land. So it is necessary to utilize sub-optimal land, namely swamp land. In addition, physiological information is needed from 10 strains of swamp rice. This study aims to determine the physiological characteristics of 10 strains of local Bengkulu swamp rice crosses of the 11th generation. This study used a single-factor complete group randomized design consisting of 10 strains of local Bengkulu swamp rice treatments namely UBPR 1, UBPR 2, UBPR 3, UBPR 4, UBPR 6, UBPR 7, UBPR 8, UBPR 9, UBPR 10 and UBPR 11. Data analysis using analysis of variance at 5% level with further Scott Knott test. The research variables consisted of specific leaf weight, net assimilation rate, plant growth rate, relative growth rate, leaf area index, plant biomass, NPK nutrient uptake. The results of the research on 10 strains of local Bengkulu swamp ric crosses showed that the specific leaf weight in weeks 3 and 4, net assimilation rate in weeks 2 and 6, plant growth rate in weeks 3, 4 and 5, relative growth rate in week 3, leaf area index in weeks 5 and 6, plant biomass and N nutrient uptake showed mixed results. UBPR 4, UBPR 7, UBPR 9 and UBPR 11 had the best values compared to other UBPR.